Composite current collector and preparation method thereof, pole piece, and sulfide solid-state battery

By using composite fluids in sulfide solid state batteries, including polymer support layer, M metal layer and anti-corrosion conductive layer, the H2S corrosion problem is solved, the cycle stability and conductive performance of the battery are improved, and the performance and cost balance is achieved .

CN118738405BActive Publication Date: 2024-12-20SHENZHEN HANKE NEW MATERIAL TECH CO LTD
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
CN202411180772.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-20
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

In sulfide solid-state batteries, sulfide reacts with trace water in the working environment to form H2S gas, corrodes traditional Cu or Al current collectors, and reduces the battery's circulation and other performance.

Method used

Using a composite fluid collection, including a polymer support layer, an M metal layer (Cu or Al) and an anti-corrosion conductive layer (Ta, Pd, Ir and other materials), the anti-corrosion conductive layer is arranged on the side of the M metal layer away from the polymer support layer. Transition and connection enhancement layers are used to optimize the structure to prevent H2S corrosion.

Benefits of technology

It improves the cycling stability and conductivity of sulfide solid-state batteries, reduces the corrosion risk of M metal layer, and balances performance and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118738405B_ABST
    Figure CN118738405B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite current collector and a preparation method thereof, a pole piece, and a sulfide solid-state battery. The composite current collector includes a polymer support layer, an M metal layer, and an anti-corrosion conductive layer; the M metal layer is arranged on the polymer support layer, the M metal contained in the M metal layer is Cu or Al, the anti-corrosion conductive layer is arranged on the side of the M metal layer away from the polymer support layer, and the material of the anti-corrosion conductive layer is selected from one or more of Ta, Pd, Ir and Rh. The outer anti-corrosion conductive layer has relatively good conductivity and can avoid being corroded by H2S, and can protect the inner Cu and Al layers to a certain extent, reduce Cu corrosion or Al surface reaction of the M metal layer, and help improve the cycle stability of the sulfide solid-state battery. Compared with the traditional copper foil or aluminum foil, the composite current collector can improve the cycle stability of the sulfide solid-state battery and can better balance the performance and cost of the composite current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage, and in particular to a composite current collector and a preparation method thereof, a pole piece, and a sulfide solid-state battery. Background Art

[0002] The ionic conductivity of sulfide solid electrolytes can reach 10 -2 S / cm level, so sulfide solid-state batteries are currently considered to be the most promising solid-state battery route for industrialization. In traditional battery pole pieces, Cu (copper) foil is mostly used as the negative electrode current collector, and Al (aluminum) foil is used as the positive electrode current collector. However, after research, for sulfide solid-state batteries, due to the material properties of sulfide itself, sulfide will react with trace water in the working environment to generate H 2 S gas, and H 2 S will corrode the Cu foil current collector and also form high-impedance substances on the surface of the positive electrode Al foil current collector, reducing the cycle performance of the sulfide solid-state battery. Summary of the invention

[0003] Based on this, it is necessary to provide a composite current collector and its preparation method, a pole piece, and a sulfide solid-state battery to solve the problem of H generated by sulfide reaction. 2 The problem of S corroding traditional Cu and Al current collectors.

[0004] The first aspect of the present invention is to provide a composite current collector, the scheme is as follows:

[0005] A composite current collector comprises a polymer support layer, an M metal layer and an anti-corrosion conductive layer; the M metal layer is arranged on the polymer support layer, the M metal contained in the M metal layer is Cu or Al, the anti-corrosion conductive layer is arranged on a side of the M metal layer away from the polymer support layer, and the material of the anti-corrosion conductive layer is selected from one or more of Ta, Pd, Ir and Rh.

[0006] In one embodiment, the composite current collector further includes a transition layer, which is disposed between the M metal layer and the anti-corrosion conductive layer. The material of the transition layer is an alloy of the M metal, and other metals in the alloy of the M metal are one or more of Ta, Pd, Ir and Rh.

[0007] In one embodiment, the atomic ratio of the M metal in the transition layer gradually decreases from a side close to the M metal layer to a side far from the M metal layer.

[0008] In one of the embodiments, the atoms of the M metal are uniformly distributed in the transition layer.

[0009] In one embodiment, the atomic proportion of the M metal in the transition layer is 45% to 55%;

[0010] In one embodiment, the thickness of the transition layer is 0.2µm~2µm.

[0011] In one embodiment, the composite current collector further includes a connection enhancement layer, which is disposed between the M metal layer and the polymer support layer, and the material of the connection enhancement layer is selected from one or more of Ti and Cr.

[0012] In one embodiment, the thickness of the connection enhancement layer is 5nm~100nm.

[0013] In one embodiment, the thickness of the M metal layer is 0.2µm~2µm.

[0014] In one embodiment, the thickness of the anti-corrosion conductive layer is 0.2µm~2µm.

[0015] In one embodiment, the thickness of the polymer support layer is 3µm~8µm.

[0016] In one of the embodiments, the material of the polymer support layer includes one or more of polyethylene, polypropylene, polyethylene terephthalate, polyimide, and polytetrafluoroethylene.

[0017] The second aspect of the present invention is to provide a method for preparing a composite current collector, the scheme is as follows:

[0018] A method for preparing a composite current collector comprises the following steps:

[0019] providing a polymer support layer;

[0020] forming an M metal layer on the polymer support layer;

[0021] An anti-corrosion conductive layer is formed on a side of the M metal layer away from the polymer support layer, and a material of the anti-corrosion conductive layer is selected from one or more of Ta, Pd, Ir and Rh.

[0022] The third aspect of the present invention is to provide a pole piece, the scheme is as follows:

[0023] A pole piece comprises an electrode layer and a composite current collector as described in any of the above embodiments or a composite current collector prepared by the preparation method as described in any of the above embodiments, wherein the electrode layer is arranged on the composite current collector.

[0024] The fourth aspect of the present invention is to provide a sulfide solid-state battery, the scheme is as follows:

[0025] A sulfide solid-state battery, comprising a positive electrode sheet, a negative electrode sheet, and a sulfide solid-state electrolyte layer arranged between the positive electrode sheet and the negative electrode sheet;

[0026] The positive electrode sheet comprises a positive electrode layer and a composite current collector as described in any of the above embodiments or a composite current collector prepared by the preparation method as described in any of the above embodiments, the positive electrode layer is arranged on the composite current collector, and the M metal is Al; and / or

[0027] The negative electrode plate includes a negative electrode layer and a composite current collector described in any of the above embodiments or a composite current collector prepared by the preparation method described in any of the above embodiments, the negative electrode layer is arranged on the composite current collector, and the M metal is Cu.

[0028] Compared with the conventional technology, the composite current collector and its preparation method, pole piece and sulfide solid-state battery have the following beneficial effects:

[0029] The composite current collector and its preparation method are provided with an M metal layer and an anti-corrosion conductive layer on a polymer support layer, and the material of the anti-corrosion conductive layer is selected from one or more of Ta, Pd, Ir and Rh. The outer anti-corrosion conductive layer has good conductivity and can avoid being 2 S corrosion, and can protect the inner Cu and Al layers to a certain extent, reduce Cu corrosion or Al surface reaction of the M metal layer, can stably collect and output current for sulfide solid-state batteries, and help improve the cycle stability of sulfide solid-state batteries. Cu and Al have better conductivity and lower cost. Therefore, compared with the traditional copper foil or aluminum foil, the above-mentioned composite current collector can improve the cycle stability of sulfide solid-state batteries and can better balance the performance and cost of the composite current collector.

[0030] The above-mentioned pole piece and sulfide solid-state battery have the composite current collector or the composite current collector prepared by the preparation method, and thus have corresponding technical characteristics and can obtain corresponding beneficial effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] FIG1 is a schematic structural diagram of a composite current collector according to an embodiment;

[0032] FIG. 2 is a schematic flow diagram of a method for preparing a composite current collector according to an embodiment.

[0033] Description of reference numerals:

[0034] 100, composite current collector; 110, polymer support layer; 120, composite conductive layer; 121, M metal layer; 122, anti-corrosion conductive layer; 123, transition layer; 124, connection enhancement layer. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0037] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0038] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0039] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0040] The present invention provides a composite current collector which is suitable for use in sulfide solid-state batteries, but is not limited thereto.

[0041] As shown in FIG. 1 , a composite current collector 100 according to an embodiment includes a polymer support layer 110 and a composite conductive layer 120 .

[0042] The composite conductive layer 120 includes an M metal layer 121 and an anti-corrosion conductive layer 122. The M metal layer 121 is disposed on the polymer support layer 110. The M metal contained in the M metal layer is Cu or Al, that is, the M metal layer is a Cu layer or an Al layer. The anti-corrosion conductive layer 122 is disposed on a side of the M metal layer 121 away from the polymer support layer 110. The material of the anti-corrosion conductive layer 122 is selected from one or more of Ta (tantalum), Pd (palladium), Ir (iridium) and Rh (rhodium).

[0043] The composite current collector 100 is provided with an M metal layer 121 and an anti-corrosion conductive layer 122 on a polymer support layer 110. The material of the anti-corrosion conductive layer 122 is selected from one or more of Ta, Pd, Ir and Rh. The outer anti-corrosion conductive layer 122 has good conductivity and can avoid being 2 S corrosion, and can protect the inner M metal layer 121 to a certain extent, reduce the corrosion of the M metal layer 121, can be stabilized for the sulfide solid-state battery to collect and output current, and help improve the cycle stability of the sulfide solid-state battery. Cu and Al have better conductivity and lower cost. Therefore, compared with the traditional copper foil or aluminum foil, the above-mentioned composite current collector 100 can improve the cycle stability of the sulfide solid-state battery and can better balance the performance and cost of the composite current collector 100.

[0044] The above-mentioned composite current collector 100 adopts a polymer support layer 110 and arranges a composite conductive layer 120 thereon. Compared with the traditional metal current collector, its weight can be reduced by 50%-80% and its thickness can be reduced by 25%-40%, thereby improving the quality and volume energy density of the battery cell. At the same time, the unique sandwich structure not only ensures the electron conduction, but the presence of the polymer support layer 110 can greatly improve the safety performance of the battery cell during mechanical abuse and internal short circuit. The density of sulfide is greater than that of traditional electrolytes, and it is necessary to reduce the mass and volume of inactive materials in the battery cell to ensure high specific energy. Therefore, the above-mentioned composite current collector 100 is used in sulfide solid-state batteries to improve the energy density and safety characteristics of the battery cell.

[0045] Exemplarily, the material of the polymer support layer 110 includes, for example, but is not limited to, one or more of PE (polyethylene), PP (polypropylene), PET (polyethylene terephthalate), PI (polyimide) and PTFE (polytetrafluoroethylene).

[0046] In some examples, the thickness of the polymer support layer 110 is 3µm to 8µm. The thickness of the polymer support layer 110 is 4µm to 7µm. Further, in some examples, the thickness of the polymer support layer 110 is 5µm to 6µm. In some specific examples, the thickness of the polymer support layer 110 is, for example, 3µm, 3.5µm, 4µm, 4.5µm, 5µm, 5.5µm, 6µm, 6.5µm, 7µm, 7.5µm, 8µm, etc.

[0047] The composite conductive layer 120 may be disposed on one side of the polymer support layer 110 or on both sides of the polymer support layer 110. In the specific example shown in FIG1 , the composite conductive layer 120 is disposed on both sides of the polymer support layer 110, respectively.

[0048] Al and Cu have good electrical conductivity and low cost. As the main conductive components of the positive and negative composite current collectors 100 , they can better balance the conductivity and cost of the composite current collectors 100 .

[0049] In some of the examples, the thickness of the M metal layer 121 is 0.2µm to 2µm. Further, in some of the examples, the thickness of the M metal layer 121 is 0.5µm to 1.5µm. Further, in some of the examples, the thickness of the M metal layer 121 is 0.8µm to 1.2µm. In some specific examples, the thickness of the M metal layer 121 is, for example, 0.2µm, 0.3µm, 0.4µm, 0.5µm, 0.6µm, 0.7µm, 0.8µm, 0.9µm, 1µm, 1.1µm, 1.2µm, 1.3µm, 1.4µm, 1.5µm, 1.6µm, 1.7µm, 1.8µm, 1.9µm, 2µm, etc.

[0050] Optionally, when the anti-corrosion conductive layer 122 includes multiple materials of the above materials, the multiple materials may be mixed with each other or may not be mixed with each other. For example, the anti-corrosion conductive layer 122 includes a film layer formed by mixing multiple materials. For another example, the anti-corrosion conductive layer 122 includes multiple sublayers of different materials stacked, more specifically, including a stacked Ta sublayer, a Pd sublayer, an Ir sublayer, a Rh sublayer, etc.

[0051] In some examples, the thickness of the anti-corrosion conductive layer 122 is 0.2µm to 2µm. Further, in some examples, the thickness of the anti-corrosion conductive layer 122 is 0.5µm to 1.2µm. Further, in some examples, the thickness of the anti-corrosion conductive layer 122 is 0.8µm to 1µm. In some specific examples, the thickness of the anti-corrosion conductive layer 122 is, for example, 0.2µm, 0.3µm, 0.4µm, 0.5µm, 0.6µm, 0.7µm, 0.8µm, 0.9µm, 1µm, 1.1µm, 1.2µm, 1.3µm, 1.4µm, 1.5µm, 1.6µm, 1.7µm, 1.8µm, 1.9µm, 2µm, etc.

[0052] As shown in FIG1 , in some examples, the composite conductive layer 120 further includes a transition layer 123. The transition layer 123 is disposed between the M metal layer 121 and the anti-corrosion conductive layer 122. The material of the transition layer 123 is an alloy of the M metal, i.e., a Cu alloy or an Al alloy, and other metals in the alloy of the M metal are one or more of Ta, Pd, Ir and Rh.

[0053] Since the conductivity of the anti-corrosion conductive layer 122 is lower than that of Cu and Al, a transition layer 123 is provided between the M metal layer 121 and the anti-corrosion conductive layer 122. The material of the transition layer 123 is an alloy of one or more of Ta, Pd, Ir and Rh and the M metal. 2 While preventing S corrosion, it is beneficial to the smooth and stable transmission of current, avoiding the formation of a high impedance area that hinders electron migration at the interface of the two layers, and also avoiding local abnormal heating caused by excessive resistance difference. At the same time, M metal as the main conductive material can better control the production cost. In addition, the transition layer 123 can also improve the interlayer bonding force between the M metal layer 121 and the anti-corrosion conductive layer 122.

[0054] In some examples, the atomic ratio of the M metal in the transition layer 123 gradually decreases from the side close to the M metal layer 121 to the side far from the M metal layer 121. By setting the atomic ratio of the M metal to change gradually, the atomic ratio of the M metal in the outer layer is small, which reduces the M metal being H 2 The probability of S corrosion is higher, and the atomic proportion of M metal is higher in the inner layer, which is beneficial to the improvement of the overall conductivity of the current collector.

[0055] The atomic percentage of the M metal on the side of the transition layer 123 close to the M metal layer 121 is, for example, 90% to 99.9%. Further, the atomic percentage of the M metal on the side of the transition layer 123 close to the M metal layer 121 is, for example, 95% to 99.9%. The atomic percentage of the M metal on the side of the transition layer 123 close to the M metal layer 121 is, for example, 98% to 99.9%.

[0056] The atomic percentage of the M metal on the side of the transition layer 123 away from the M metal layer 121 is, for example, 0.1% to 10%. Further, the atomic percentage of the M metal on the side of the transition layer 123 away from the M metal layer 121 is, for example, 0.1% to 5%. Further, the atomic percentage of the M metal on the side of the transition layer 123 away from the M metal layer 121 is, for example, 0.1% to 2%.

[0057] Optionally, the atomic ratio of the M metal in the transition layer 123 may be gradually changed from one side to the other, or may be gradually changed from one side to the other.

[0058] In other examples, the M metal atoms in the transition layer 123 may also be uniformly distributed.

[0059] In some of the examples, the atomic percentage of M metal in the transition layer 123 is 45% to 55%. Further, in some of the examples, the atomic percentage of M metal in the transition layer 123 is 47% to 53%. Further, in some of the examples, the atomic percentage of M metal in the transition layer 123 is 49% to 51%. Further, in some of the examples, the atomic percentage of M metal in the transition layer 123 is 50%. In some specific examples, the atomic percentage of M metal in the transition layer 123 is, for example, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, etc.

[0060] In some examples, the other metal in the M metal alloy of the transition layer 123 is the same as the metal in the anti-corrosion conductive layer 122. In other examples, the other metal in the M metal alloy of the transition layer 123 is different from the metal in the anti-corrosion conductive layer 122.

[0061] In some of the examples, the thickness of the transition layer 123 is 0.2µm to 2µm. Further, in some of the examples, the thickness of the transition layer 123 is 0.5µm to 1.5µm. Further, in some of the examples, the thickness of the transition layer 123 is 0.8µm to 1.2µm. In some specific examples, the thickness of the transition layer 123 is, for example, 0.2µm, 0.3µm, 0.4µm, 0.5µm, 0.6µm, 0.7µm, 0.8µm, 0.9µm, 1µm, 1.1µm, 1.2µm, 1.3µm, 1.4µm, 1.5µm, 1.6µm, 1.7µm, 1.8µm, 1.9µm, 2µm, etc.

[0062] As shown in Fig. 1, in some examples, the composite conductive layer 120 further includes a connection enhancement layer 124. The connection enhancement layer 124 is disposed between the M metal layer 121 and the polymer support layer 110. The material of the connection enhancement layer 124 is selected from one or more of Ti (titanium) and Cr (chromium).

[0063] Through experimental research, it is found that the connection effect between Ti and Cr and polymer is better than that between Cu and Al. Using at least one of Ti and Cr as the bonding agent can enhance the connection force between the polymer support layer 110 and the M metal layer 121, and can improve the problem of the conductive layer falling off during the volume change of the battery cell.

[0064] Optionally, when the connection enhancement layer 124 includes multiple materials of the above materials, the multiple materials may be mixed with each other or may not be mixed with each other. For example, the connection enhancement layer 124 includes a film layer formed by mixing multiple materials. For another example, the connection enhancement layer 124 includes multiple sublayers of different materials stacked, more specifically, a Ti sublayer and a Cr sublayer stacked.

[0065] After experimental research, the thickness of the above-mentioned connection enhancement layer 124 is nanometer level, that is, it can effectively enhance the connection force between the polymer support layer 110 and the M metal layer 121. On this basis, the thickness of the connection enhancement layer 124 is set to nanometer level, enhances the interlayer force, and controls the cost. In some examples, the thickness of the connection enhancement layer 124 is 5nm~100nm. Further, in some examples, the thickness of the connection enhancement layer 124 is 10nm~60nm. Further, in some examples, the thickness of the connection enhancement layer 124 is 20nm~40nm. In some specific examples, the thickness of the connection enhancement layer 124 is, for example, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, etc.

[0066] Furthermore, the present invention also provides a method for preparing any of the above-mentioned composite current collectors 100.

[0067] The preparation method of the composite current collector 100 of one embodiment includes the following steps:

[0068] Step S110 , providing a polymer support layer 110 .

[0069] Step S130 , forming an M metal layer 121 on the polymer support layer 110 .

[0070] Step S150 , forming an anti-corrosion conductive layer 122 on a side of the M metal layer 121 away from the polymer support layer 110 , wherein the material of the anti-corrosion conductive layer 122 is selected from one or more of Pt, In and Ta.

[0071] The preparation method of the composite current collector 100 is to set an M metal layer 121 and an anti-corrosion conductive layer 122 on a polymer support layer 110. The material of the anti-corrosion conductive layer 122 is selected from one or more of Ta, Pd, Ir and Rh. The outer anti-corrosion conductive layer 122 has good conductivity and can avoid being H 2 S corrosion, and can protect the inner M metal layer 121 to a certain extent, reduce the corrosion of the M metal layer 121, can be stabilized for the sulfide solid-state battery to collect and output current, and help improve the cycle stability of the sulfide solid-state battery. Cu and Al have better conductivity and lower cost. Therefore, compared with the traditional copper foil or aluminum foil, the above-mentioned composite current collector 100 can improve the cycle stability of the sulfide solid-state battery and can better balance the performance and cost of the composite current collector 100.

[0072] In step S130 , the M metal layer 121 may be prepared by physical vapor deposition (PVD), chemical plating, electroplating and other processes. The physical vapor deposition process may be magnetron sputtering, evaporation and other processes.

[0073] In step S150 , the anti-corrosion conductive layer 122 may be prepared by a physical vapor deposition process, such as magnetron sputtering, evaporation, and the like.

[0074] In some examples, the anti-corrosion conductive layer 122 is prepared by a magnetron sputtering process, and a multi-target magnetron sputtering device can be used for coating. During coating, the deposition chamber is evacuated to 1×10 -4 Pa, introduce an inert gas (such as argon) with a flow rate of 60sccm~100sccm, control the working gas pressure to 0.1Pa~5Pa, and the working power to 50W~200W.

[0075] In some examples, before step S130, the method for preparing the composite current collector 100 includes the following steps:

[0076] Step S120: forming a connection enhancement layer 124 on the polymer support layer 110. The material of the connection enhancement layer 124 is selected from one or more of Ti and Cr.

[0077] In the above example, the connection enhancement layer 124 is disposed between the M metal layer 121 and the polymer support layer 110 .

[0078] In step S120 , the connection enhancement layer 124 may be prepared by a physical vapor deposition process, such as magnetron sputtering, evaporation, and the like.

[0079] In some examples, the connection enhancement layer 124 is prepared by a magnetron sputtering process. During the deposition, the deposition chamber is evacuated to a vacuum of 1×10 -4Pa, introduce an inert gas (such as argon) with a flow rate of 60sccm~100sccm, control the working gas pressure to 0.1Pa~5Pa, and the working power to 50W~200W.

[0080] In some examples, before step S150, the method for preparing the composite current collector 100 includes the following steps:

[0081] Step S140, forming a transition layer 123 on the side of the M metal layer 121 away from the polymer support layer 110. The material of the transition layer 123 is an alloy of the M metal, and other metals in the alloy of the M metal are one or more of Ta, Pd, Ir and Rh.

[0082] In the above example, the transition layer 123 is disposed between the M metal layer 121 and the anti-corrosion conductive layer 122 .

[0083] In step S140 , the transition layer 123 may be prepared by a physical vapor deposition process, such as magnetron sputtering, evaporation, and the like.

[0084] In some examples, the transition layer 123 is prepared by a magnetron sputtering process, and a multi-target magnetron sputtering device can be used for coating. During coating, the deposition chamber is evacuated to 1×10 -4 Pa, introduce an inert gas (such as argon) with a flow rate of 60sccm~100sccm, control the working gas pressure to 0.1Pa~5Pa, and the working power to 50W~200W.

[0085] As shown in FIG. 2 , in some examples, the method for preparing the composite current collector 100 includes the following steps:

[0086] Step S110 , providing a polymer support layer 110 .

[0087] Step S120 , forming a connection enhancement layer 124 on the polymer support layer 110 .

[0088] Step S130 , forming an M metal layer 121 on a side of the connection enhancement layer 124 away from the polymer support layer 110 .

[0089] Step S140 , forming a transition layer 123 on a side of the M metal layer 121 away from the connection enhancement layer 124 .

[0090] Step S150 , forming an anti-corrosion conductive layer 122 on a side of the transition layer 123 away from the M metal layer 121 .

[0091] Furthermore, the present invention also provides a pole piece, which is suitable for use in sulfide solid-state batteries, but is not limited thereto.

[0092] The pole piece of one embodiment includes an electrode layer and the composite current collector 100 of any of the above examples or the composite current collector 100 prepared by the preparation method of any of the above examples. The electrode layer is disposed on the composite current collector 100 .

[0093] The pole piece has the composite current collector 100 of any of the above examples or the composite current collector 100 prepared by the preparation method of any of the above examples, and thus has corresponding technical features and can obtain corresponding beneficial effects.

[0094] Optionally, the electrode sheet may be a positive electrode sheet or a negative electrode sheet.

[0095] In some examples, the electrode sheet is a positive electrode sheet. Accordingly, the electrode layer is a positive electrode layer. In the positive electrode sheet, the M metal in the composite current collector 100 is preferably Al.

[0096] In some of these examples, the cathode layer includes a mixed cathode material and a sulfide.

[0097] For example, the positive electrode material includes LiNi 0.5 Co 0.2 Mn 0.3 O 2 、LiNi 0.6 Co 0.1 Mn 0.3 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.9 Co 0.05 Mn 0.05 O 2 One or more of .

[0098] For example, the sulfide may be, but is not limited to, Li 6 PS 5 Cl materials, Li 10 G 2 S 12 Materials, Li 3 PS 4 Materials, etc.

[0099] It can be understood that the positive electrode layer may further include a positive electrode binder, a positive electrode conductor, and the like.

[0100] Illustratively, the positive electrode binder includes one or more of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, epoxy resin and nylon.

[0101] Illustratively, the positive electrode conductive agent includes one or more of carbon black, acetylene black, and Ketjen black.

[0102] In some of the examples, the positive electrode layer contains 65-75 parts by weight of positive electrode material, 24-28 parts by weight of sulfide, 1-3 parts by weight of positive electrode binder and 1-3 parts by weight of positive electrode conductor, with a total weight of 100 parts. In a specific example, the positive electrode layer contains 70 parts by weight of positive electrode material, 26 parts by weight of sulfide, 2 parts by weight of positive electrode binder and 2 parts by weight of positive electrode conductor. Among them, the positive electrode material is preferably LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.9 Co 0.05 Mn 0.05 O 2 At least one of the following. The sulfide is preferably Li 6 PS 5 Cl, Li 10 G 2 S 12 , Li 3 PS 4 At least one of the materials.

[0103] In some of these examples, the surface density of the active material in the cathode layer is 8 mg / cm 2 ~15mg / cm 2 Furthermore, in some of the examples, the surface density of the active material in the positive electrode layer is 10 mg / cm 2 ~13mg / cm 2 In some specific examples, the surface density of the active material in the positive electrode layer is, for example, 8 mg / cm 2 、8.5mg / cm 2 , 9mg / cm 2 、9.5mg / cm 2 、10mg / cm 2 、10.5mg / cm 2 、11mg / cm 2 、11.5mg / cm 2 , 12mg / cm 2 , 12.5mg / cm 2 、13mg / cm 2、13.5mg / cm 2 、14mg / cm 2 、14.5mg / cm 2 、15mg / cm 2 wait.

[0104] In some examples, the electrode sheet is a negative electrode sheet. Accordingly, the electrode layer is a negative electrode layer. In the negative electrode sheet, the M metal in the composite current collector 100 is preferably Cu.

[0105] The negative electrode layer contains a negative electrode material. Exemplarily, the negative electrode material includes one or more of natural graphite, artificial graphite, micron silicon material, soft carbon, hard carbon, lithium metal, lithium metal alloy and transition metal oxide.

[0106] It can be understood that the negative electrode layer may further include a negative electrode binder, a negative electrode conductor, and the like.

[0107] Illustratively, the negative electrode binder includes one or more of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, epoxy resin and nylon.

[0108] Illustratively, the negative electrode conductive agent includes one or more of carbon black, acetylene black and Ketjen black.

[0109] In some examples, the negative electrode layer contains 94-98 parts by weight of negative electrode material, 1-3 parts by weight of negative electrode binder and 1-3 parts by weight of negative electrode conductor, with a total weight of 100 parts. In a specific example, the negative electrode layer contains 97 parts by weight of negative electrode material, 2 parts by weight of negative electrode binder and 1 part by weight of negative electrode conductor. The negative electrode material is preferably a micron silicon material.

[0110] In some of these examples, the surface density of the active material in the negative electrode layer is 0.3 mg / cm 2 ~0.6mg / cm 2 Furthermore, in some of the examples, the surface density of the active material in the negative electrode layer is 0.4 mg / cm 2 ~0.5mg / cm 2 In some specific examples, the surface density of the active material in the negative electrode layer is, for example, 0.3 mg / cm 2 , 0.32mg / cm 2 , 0.35mg / cm 2 , 0.38mg / cm 2 , 0.4mg / cm 2 , 0.42mg / cm 2 , 0.45mg / cm2 、0.48mg / cm 2 , 0.5mg / cm 2 , 0.52mg / cm 2 , 0.55mg / cm 2 、0.58mg / cm 2 , 0.6mg / cm 2 wait.

[0111] The positive electrode sheet is prepared by dry-mixing the corresponding active material, binder and conductive agent at 80°C for 2 hours, and applying the positive electrode coating on the composite current collector 100 by hot pressing to form the corresponding positive electrode layer; the negative electrode sheet can be prepared by mixing and dispersing the corresponding active material, binder and conductive agent in a solvent to obtain a slurry, and then coating the slurry on the composite current collector 100, and then drying to remove the solvent to form the corresponding negative electrode layer on the composite current collector 100.

[0112] Furthermore, the present invention also provides a sulfide solid-state battery.

[0113] A sulfide solid-state battery in one embodiment includes a positive electrode sheet, a negative electrode sheet, and a sulfide solid-state electrolyte layer disposed between the positive electrode sheet and the negative electrode sheet.

[0114] In some of the examples, the positive electrode sheet includes a positive electrode layer and a composite current collector 100 of any of the above examples or a composite current collector 100 prepared by a preparation method of any of the above examples, and the positive electrode layer is disposed on the composite current collector 100 .

[0115] In some of the examples, the negative electrode plate includes a negative electrode layer and a composite current collector 100 of any of the above examples or a composite current collector 100 prepared by a preparation method of any of the above examples, and the negative electrode layer is disposed on the composite current collector 100 .

[0116] The above-mentioned sulfide solid-state battery has the composite current collector 100 of any of the above-mentioned examples, and thus has corresponding technical features and can obtain corresponding beneficial effects.

[0117] In some examples, the sulfide solid electrolyte layer includes a binder and a solid electrolyte layer. The solid electrolyte layer includes a sulfide solid electrolyte.

[0118] Illustratively, the binder is PTFE.

[0119] For example, the sulfide solid electrolyte includes Li 6 PS 5 Cl, Li 10 G 2 S 12 , Li3 PS 4 One or more of .

[0120] It is understandable that the sulfide solid electrolyte layer may also include a binder mixed with the sulfide solid electrolyte. In some of these examples, the mass ratio of the sulfide solid electrolyte to the binder is 90:1~99.9:0.1. Further, in some of these examples, the mass ratio of the sulfide solid electrolyte to the binder is 95:1~99.9:0.1. Further, in some of these examples, the mass ratio of the sulfide solid electrolyte to the binder is 98:2~99.5:0.5. Further, in some of these examples, the mass ratio of the sulfide solid electrolyte to the binder is 99:1.

[0121] Illustratively, the binder includes one or more of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, epoxy resin and nylon.

[0122] In some of the examples, the thickness of the solid electrolyte layer is 20µm to 100µm. Further, in some of the examples, the thickness of the solid electrolyte layer is 30µm to 80µm. Further, in some of the examples, the thickness of the solid electrolyte layer is 40µm to 60µm. In some specific examples, the thickness of the solid electrolyte layer is 20µm, 25µm, 30µm, 35µm, 40µm, 45µm, 50µm, 55µm, 60µm, 65µm, 70µm, 75µm, 80µm, 85µm, 90µm, 95µm, 100µm, etc.

[0123] The following specific examples are provided to further illustrate the present invention. The present invention provides the following specific examples for a better understanding of the present invention, but is not limited to the specific implementation methods and does not limit the protection scope of the present invention.

[0124] Example 1

[0125] This embodiment provides a composite current collector and a preparation method thereof.

[0126] The preparation method of the composite current collector for the negative electrode of this embodiment comprises the following steps:

[0127] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0128] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10-4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0129] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0130] Step 4: The working power is adjusted to 70 W, and a Cu50-Pd50 alloy layer (Cu50-Pd50 means that the proportion of Cu and Pd atoms is 50%, the same below) is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 µm.

[0131] Step 5: The working power is adjusted to 100 W, and a Pd layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0132] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0133] Example 2

[0134] This embodiment provides a composite current collector and a preparation method thereof.

[0135] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0136] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0137] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 20 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0138] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0139] Step 4: The working power is adjusted to 70 W, and a Cu50-Pd50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 µm.

[0140] Step 5: The working power is adjusted to 100 W, and a Pd layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0141] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0142] Example 3

[0143] This embodiment provides a composite current collector and a preparation method thereof.

[0144] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0145] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0146] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0147] Step 3: Continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1.2µm, and the operating power is 150W.

[0148] Step 4: The working power is adjusted to 70 W, and a Cu50-Pd50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 µm.

[0149] Step 5: The working power is adjusted to 100 W, and a Pd layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0150] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0151] Example 4

[0152] This embodiment provides a composite current collector and a preparation method thereof.

[0153] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0154] In step 1, a PET (polyethylene terephthalate) film having a thickness of 3 µm is provided as a polymer support layer.

[0155] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0156] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0157] Step 4: The working power is adjusted to 70 W, and a Cu50-Pd50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 µm.

[0158] Step 5: The working power is adjusted to 100 W, and a Pd layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0159] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0160] Example 5

[0161] This embodiment provides a composite current collector and a preparation method thereof.

[0162] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0163] Step 1, providing a PP (polypropylene) film with a thickness of 3µm as a polymer support layer.

[0164] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0165] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0166] Step 4: The working power is adjusted to 70 W, and a Cu50-Pd50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 µm.

[0167] Step 5: The working power is adjusted to 100 W, and a Pd layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0168] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0169] Example 6

[0170] This embodiment provides a composite current collector and a preparation method thereof.

[0171] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0172] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0173] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0174] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0175] Step 4: The working power is adjusted to 70 W, and a Cu50-Ir50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 μm.

[0176] Step 5: The working power is adjusted to 100 W, and an Ir layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0177] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0178] Example 7

[0179] This embodiment provides a composite current collector and a preparation method thereof.

[0180] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0181] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0182] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 20 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0183] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0184] Step 4: The working power is adjusted to 70 W, and a Cu50-Ir50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 μm.

[0185] Step 5: The working power is adjusted to 100 W, and an Ir layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0186] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0187] Example 8

[0188] This embodiment provides a composite current collector and a preparation method thereof.

[0189] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0190] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0191] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0192] Step 3: Continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1.2µm, and the operating power is 150W.

[0193] Step 4: The working power is adjusted to 70 W, and a Cu50-Ir50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 μm.

[0194] Step 5: The working power is adjusted to 100 W, and an Ir layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0195] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0196] Example 9

[0197] This embodiment provides a composite current collector and a preparation method thereof.

[0198] The preparation method of the composite current collector for the negative electrode of this embodiment comprises the following steps:

[0199] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0200] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0201] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0202] Step 4: The working power is adjusted to 70 W, and a Cu50-Ta50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 μm.

[0203] Step 5: The working power is adjusted to 100 W, and a Ta layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0204] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0205] Example 10

[0206] This embodiment provides a composite current collector and a preparation method thereof.

[0207] The preparation method of the composite current collector for the negative electrode of this embodiment comprises the following steps:

[0208] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0209] Step 2: Deposit a Ti layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 20 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0210] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0211] Step 4: The working power is adjusted to 70 W, and a Cu50-Ta50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 μm.

[0212] Step 5: The working power is adjusted to 100 W, and a Ta layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0213] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0214] Embodiment 11

[0215] This embodiment provides a composite current collector and a preparation method thereof.

[0216] The preparation method of the composite current collector for the negative electrode of this embodiment comprises the following steps:

[0217] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0218] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0219] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0220] Step 4: The working power is adjusted to 70 W, and a Cu50-Rh50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 μm.

[0221] Step 5: The working power is adjusted to 100 W, and a Rh layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0222] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0223] Example 12

[0224] This embodiment provides a composite current collector and a preparation method thereof.

[0225] The preparation method of the composite current collector for the negative electrode of this embodiment comprises the following steps:

[0226] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0227] Step 2: Deposit a Ti layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 20 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0228] Step 3, continue to deposit a Cu layer on the side of the connection enhancement layer away from the polymer support layer to form an M metal layer with a thickness of 1µm, and the operating power is 150W.

[0229] Step 4: The working power is adjusted to 70 W, and a Cu50-Rh50 alloy layer is deposited on the side of the M metal layer away from the connection enhancement layer to form a transition layer with a thickness of 0.3 μm.

[0230] Step 5: The working power is adjusted to 100 W, and a Rh layer is deposited on the side of the transition layer away from the M metal layer to form an anti-corrosion conductive layer with a thickness of 0.3 µm.

[0231] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3 and step 4. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0232] Embodiment 13

[0233] This embodiment provides a composite current collector and a preparation method thereof.

[0234] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0235] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0236] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0237] Step 3, continue to deposit an M metal layer on the side of the connection enhancement layer away from the polymer support layer, with a thickness of 1µm and an operating power of 150W.

[0238] Step 4: Change the target material to a Pd target material, adjust the working power to 100 W, and deposit a Pd layer on the side of the M metal layer away from the connection enhancement layer to form an anti-corrosion conductive layer with a thickness of 0.6 µm.

[0239] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0240] Embodiment 14

[0241] This embodiment provides a composite current collector and a preparation method thereof.

[0242] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0243] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0244] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0245] Step 3, continue to deposit an M metal layer on the side of the connection enhancement layer away from the polymer support layer, with a thickness of 1.3µm and an operating power of 150W.

[0246] Step 4: Change the target material to a Pd target material, adjust the working power to 100 W, and deposit a Pd layer on the side of the M metal layer away from the connection enhancement layer to form an anti-corrosion conductive layer with a thickness of 0.6 µm.

[0247] The difference between the preparation method of the composite current collector for the positive electrode of this embodiment and the composite current collector for the negative electrode described above is that the M metal is replaced with Al in step 3. The relevant parameters of the composite current collectors for the positive and negative electrodes of this embodiment are shown in Table 1.

[0248] Comparative Example 1

[0249] The current collector for the negative electrode provided in this comparative example is a copper foil with a thickness of 6 μm.

[0250] The current collector for the positive electrode provided in this comparative example is an aluminum foil with a thickness of 8µm.

[0251] Comparative Example 2

[0252] The preparation method of the current collector provided in this comparative example comprises the following steps:

[0253] Step 1, providing a PI (polyimide) film with a thickness of 3µm as a polymer support layer.

[0254] Step 2: Deposit a Cr layer on both sides of the polymer support layer by magnetron sputtering to form a connection enhancement layer with a thickness of 10 nm. During the coating process, the deposition chamber was evacuated to 1×10 -4 Pa, introduce argon gas with a flow rate of 80sccm, control the working gas pressure to 0.1Pa, and the working power to 50W.

[0255] Step 3, continue to deposit an M metal layer on the side of the connection enhancement layer away from the polymer support layer, with a thickness of 1µm and an operating power of 150W.

[0256] The difference between the preparation method of the composite current collector for the positive electrode in this comparative example and the composite current collector for the negative electrode is that the M metal is replaced with Al in step 3. The relevant parameters of the composite current collectors for the positive and negative electrodes in this comparative example are shown in Table 1.

[0257] The composite current collectors prepared in the above examples and comparative examples are applied to sulfide solid-state batteries.

[0258] Specifically, the sulfide solid-state battery is prepared according to the following steps.

[0259] Step 1, preparation of negative electrode sheet:

[0260] The micron silicon material, conductive carbon black, and PAA binder were weighed in a mass ratio of 97:1:2 and wet mixed to prepare a negative electrode slurry. The negative electrode slurry was coated on the composite current collector for the negative electrode prepared in the above embodiment and comparative example to form a negative electrode layer. The surface density of the active material in the negative electrode layer was 0.36 mg / cm 2 .

[0261] Step 2, preparation of positive electrode sheet:

[0262] The positive electrode current collector uses PET with a thickness of 6 μm as the polymer support layer, and Al foils with a thickness of 1 μm are respectively set on both sides of the polymer support layer.

[0263] NCM811, LPSCl, conductive carbon black and PTFE binder were weighed in a mass ratio of 70:26:2:2, and dry mixed at 80°C for 2h. The positive electrode material was coated on the composite current collector for positive electrode prepared in the above embodiment and comparative example by hot pressing to form a positive electrode layer. The surface density of the positive electrode active material in the positive electrode layer was 10mg / cm 2 .

[0264] Step 3, preparation of sulfide solid electrolyte layer:

[0265] The electrolyte Li 6 PS 5 Cl and PTFE binder were weighed in a mass ratio of 99:1, and dry mixed at 80°C for 2h. After the pressing roller was heated to 80°C, the electrolyte slurry was coated on the PET film by hot pressing to form an electrolyte membrane with a thickness of 50µm.

[0266] Step 4, preparation of sulfide solid-state battery:

[0267] The positive electrode sheet, sulfide solid electrolyte layer and negative electrode sheet are stacked in sequence to form a soft-pack battery.

[0268] The following performance tests were performed on the composite current collectors prepared in the above embodiments and comparative examples and the corresponding sulfide solid-state batteries.

[0269] 1. The tensile strength of the current collector is tested by:

[0270] Take three samples with a special test die, place the samples between the test fixtures and fix them, and use a computer to control the universal tensile testing machine to stretch the fixtures outward until the samples break, and record the readings.

[0271] 2. Cycle performance of solid-state batteries, the test method is:

[0272] Use the Xinwei battery test cabinet to perform room temperature cycle tests under the 0.2C / 0.2C charge and discharge protocol, and record the number of cycles when the battery capacity decays to 80% of the initial capacity.

[0273] The test results are shown in Table 1.

[0274] Table 1 Tensile strength of current collectors prepared in Examples and Comparative Examples and cycle performance of sulfide solid-state batteries

[0275]

[0276] It can be seen from the test results in Table 1 that, compared with Comparative Examples 1 and 2, the cycle performance of the sulfide solid-state battery using the current collectors of Examples 1 to 14 is significantly improved, indicating that the scheme of the present invention can better prevent the current collector from contacting H by setting anti-corrosion conductive layers such as Ta, Pd, Ir and Rh. 2 S reacts and is corroded or produces high-impedance materials, which can stably collect and output current for sulfide solid-state batteries, helping to improve the cycle stability of sulfide solid-state batteries.

[0277] By comparing the test results of Examples 1 and 13, it can be seen that the cycle performance of the sulfide solid-state battery using the current collector of Example 1 is improved compared with that of Example 13. Since there is no transition layer in the current collector of Example 13 and there is a difference in conductivity between the anti-corrosion conductive layer and the M metal layer, a high-impedance area that hinders electron migration is easily formed at the interface between the two layers, thereby affecting the battery cycle performance.

[0278] By comparing the test results of Examples 1 and 14, it can be seen that the cycle performance of the sulfide solid-state battery using the current collector of Example 1 is improved compared with that of Example 14. Since there is no transition layer in the current collector of Example 14 and there is a difference in conductivity between the anti-corrosion conductive layer and the M metal layer, a high impedance area that hinders electron migration is easily formed at the interface between the two layers, thereby affecting the battery cycle performance.

[0279] Comparing the test results of Examples 1, 4 and 5, it can be seen that the material of the polymer support layer also has a certain influence on the tensile strength of the current collector and the cycle performance of the sulfide solid-state battery. Among them, when the polymer support layer adopts PI and PP, the cycle performance of the sulfide solid-state battery is significantly better than PET. When the polymer support layer adopts PI, the tensile strength of the current collector is significantly better than PP. The higher the tensile strength of the current collector, the more conducive it is to the subsequent processing and manufacturing of the pole piece. Taking all factors into consideration, PI is preferably used for the polymer support layer.

[0280] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0281] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A sulfide solid-state battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet, and a sulfide solid electrolyte layer arranged between the positive electrode sheet and the negative electrode sheet; The positive electrode sheet comprises a positive electrode layer and a composite current collector, wherein the positive electrode layer is arranged on the composite current collector; The composite current collector includes a polymer support layer, an M metal layer and an anti-corrosion conductive layer; the M metal layer is arranged on the polymer support layer, the M metal contained in the M metal layer is Al, the anti-corrosion conductive layer is arranged on the side of the M metal layer away from the polymer support layer, and the material of the anti-corrosion conductive layer is Ta; the composite current collector also includes a transition layer, the transition layer is arranged between the M metal layer and the anti-corrosion conductive layer, the material of the transition layer is an alloy of the M metal, and the other metals in the alloy of the M metal are Ta; the atomic proportion of the M metal in the transition layer gradually decreases from the side close to the M metal layer to the side away from the M metal layer; the thickness of the M metal layer is 0.2µm~2µm, the thickness of the transition layer is 0.2µm~2µm, the thickness of the anti-corrosion conductive layer is 0.2µm~2µm, and the thickness of the polymer support layer is 3µm~8µm.

2. The sulfide solid-state battery according to claim 1, characterized in that: The material of the polymer support layer includes one or more of polyethylene, polypropylene, polyethylene terephthalate, polyimide, and polytetrafluoroethylene.

3. The sulfide solid-state battery according to claim 2, characterized in that: The atomic proportion of the M metal in the transition layer is 45% to 55%.

4. The sulfide solid-state battery according to any one of claims 1 to 3, characterized in that The composite current collector further includes a connection enhancement layer, which is disposed between the M metal layer and the polymer support layer. The material of the connection enhancement layer is selected from one or more of Ti and Cr.

5. The sulfide solid-state battery according to claim 4, characterized in that: The thickness of the connection enhancement layer is 5nm-100nm.